2018
DOI: 10.1038/s41598-018-35893-4
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming degradation in spatial multiplexing systems with stochastic nonlinear impairments

Abstract: Single-mode optical fibres now underpin telecommunication systems and have allowed continuous increases in traffic volume and bandwidth demand whilst simultaneously reducing cost- and energy-per-bit over the last 40 years. However, it is now recognised that such systems are rapidly approaching the limits imposed by the nonlinear Kerr effect. To address this, recent research has been carried out into mitigating Kerr nonlinearities to increase the nonlinear threshold and into spatial multiplexing to offer additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Section IV presents and analyzes simulation results for the different transmission models in section II over a wide range of DMD and XT values; extending our previous results by considering a larger number of WDM channels over span lengths optimized to minimize power consumption [39,40]. Section V extends our recent results on the application of DBP to WDM-SDM systems [41][42][43] by: (i) analyzing the dependency on the number of back-propagated channels; (ii) considering a wider range of LMC and DMD scenarios; (iii) extending the characterization of the GD spreading in the strong LMC regime. Section VI draws the final conclusions.…”
Section: Introductionmentioning
confidence: 59%
“…Section IV presents and analyzes simulation results for the different transmission models in section II over a wide range of DMD and XT values; extending our previous results by considering a larger number of WDM channels over span lengths optimized to minimize power consumption [39,40]. Section V extends our recent results on the application of DBP to WDM-SDM systems [41][42][43] by: (i) analyzing the dependency on the number of back-propagated channels; (ii) considering a wider range of LMC and DMD scenarios; (iii) extending the characterization of the GD spreading in the strong LMC regime. Section VI draws the final conclusions.…”
Section: Introductionmentioning
confidence: 59%
“…Please see [33] for uncoupled NL coefficients. When considering different DMD values, we simply scale the GD vector in Table 1 instead of re-optimising the profile to avoid changing other fibre characteristics (as in [18]). For full details on the simulation setup, channel estimation and equalization please see [18].…”
Section: Models Comparisonmentioning
confidence: 99%
“…When considering different DMD values, we simply scale the GD vector in Table 1 instead of re-optimising the profile to avoid changing other fibre characteristics (as in [18]). For full details on the simulation setup, channel estimation and equalization please see [18]. Finally, after transmission, the Q-factor of the centre channel is estimated using the mean and standard deviation of the received symbols [34].…”
Section: Models Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…systems has been under study [36,37] having been shown that their impact is non-negligible. As a consequence, the investigation of applying digital back propagation (DBP) to address the IM-NL penalties in SDM systems has attracted interest [38][39][40][41] showing that considerable improvements can be achieved for weak to intermediate linear coupling regime [39] and identifying cases where increasing DBP bandwidth towards full field compensation degrades the performance [41]. In this paper, we explore alternative ways of implementing the nonlinear compensation step in the split-step Fourier method (SSFM) for SDM systems which are characterized by significant decorrelation (as induced by DMD and LMC) between the spatial-and wavelength-division-multiplexed (WDM) channels.…”
Section: Introductionmentioning
confidence: 99%